1979
DOI: 10.1007/bf01479989
|View full text |Cite
|
Sign up to set email alerts
|

Renales Kallikrein-Kinin-System und Blutdruckregulation

Abstract: Kallikrein excreted with the urine appears to be formed in the kidney. The kallikrein-kinin system in the kidney is localized in the distal nephron from the juxtaglomerular apparatus to the collecting duct. It has been shown that intrarenal infusion of kinins produces an increase in renal blood flow as well as diuresis and natriuresis. Part of the effect of kinins appears to be mediated by the release of prostaglandins. However, the precise role of the renal kallikrein-kinin system in sodium and volume homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Urinary excretion of prostaglandin E was found to be decreased in such patients [1,152,167]. Nevertheless, the role of renal prostaglandin E in blood pressure regulation has been disputed, and it-is presently unknown whether vasodilatator prostaglandins of vascular origin such as PGI2 and 6-Keto-PGFI= [123], the vasoconstrictor substance PGFI= (123,153) or certain components of the kallikrein&inin system [53] may be deficient in hypertension.…”
Section: Pressor Factors As Related To Cardiovascular Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary excretion of prostaglandin E was found to be decreased in such patients [1,152,167]. Nevertheless, the role of renal prostaglandin E in blood pressure regulation has been disputed, and it-is presently unknown whether vasodilatator prostaglandins of vascular origin such as PGI2 and 6-Keto-PGFI= [123], the vasoconstrictor substance PGFI= (123,153) or certain components of the kallikrein&inin system [53] may be deficient in hypertension.…”
Section: Pressor Factors As Related To Cardiovascular Reactivitymentioning
confidence: 99%
“…1). Whether or not a deficiency in vasodepressor hormones [53,89,104,123] may contribute to certain forms of hypertension is presently unclear.…”
Section: Abstract: Essential Hypertension -Hypertensionmentioning
confidence: 99%
“…7 It is an acute phase protein functioning both as a potent cysteine protease inhibitor and a precursor of vasoactive peptide T-kinin that is the most abundant kinin in rat. 8 The kinin system is one of the endogenous vasodepressor systems that plays a role in blood pressure control 9 and generation of potent vasodilating peptides. Majima and co-workers [10][11][12] have reported that kininogen-deficient Brown Norway Katholiek rats became hypertensive earlier than the normal Brown Norway rats when subjected to diet-elevating blood pressure.…”
mentioning
confidence: 99%